Remnant intrapancreatic choledochal cyst with symptomatic cystolithiasis - Muthalampet, Karthi; Anbalagan, Amudhan; Shanmugasundaram, Rajendran (International Surgery Journal, 2019)
A young female who had undergone choledochal cyst excision as a child presented with retained stone in the remnant intrapancreatic choledochal cyst which caused acute pancreatitis. This case is being reported to emphasise the importance of excising the choledochal cyst through the entire dilated part and to report the possibility of patients having symptoms due to protein plugs or retained stone in the intrapancreatic remnant.